Frugal engineering of a jaw crusher using the factor-of-frugality, a modern version of the safety-factor - Aditya Krishnan; Balkrishna C. Rao (PLoS ONE, 2025)
Businesses are increasingly keen on going frugal due to increasing demand for sustainable and low-cost products that do not sacrifice quality. However, there is a dearth of tools for the systematic design and engineering of frugal products from scratch in the industry. Accordingly, a new approach has been applied in this paper for the formal design of a frugal jaw crusher for the mining industry. Consequently, this paper uses the factor of frugality (F of FN) which is a composite number that combines the safety factor (N) with fractions of material saved in various stages of product-development. In doing so, this work has iteratively applied the factor of frugality to the relevant components of a jaw crusher. And rigorous design procedures are adopted, for maintaining quality, due to the use of lower safety factors in making the product frugal. Contemporary concepts like generative design, design for manufacturing and biomimetics have been explored to achieve frugality in the relevant “bulky” components of a jaw crusher. Accordingly, factors of frugality of 1.871.79, 1.761.68 and 1.631.33 have been obtained for the flywheel, the Pitman and the rear wall, respectively, based on the frugal approach. Therefore, use of the new frugal design approach has resulted in material savings of 8%, 7% and 30% and increases in factor of safety of 35%, 71% and 18% in the flywheel, the Pitman and the rear wall, respectively, over their base values. Such savings in materials have been accompanied by moderate cost reductions with improvement in functionality and this trio of features is typical of an advanced frugal product.